KETERSEDIAAN RUANG TERBUKA HIJAU DAN URBAN HEAT ISLAND DI KOTA MAKASSAR - Rindi Kurnianti (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2020)
Urban Heat Island (UHI) is a phenomenon where temperature in urban areas relatively increased compared to rural areas, and is occured in many major cities of the world including Indonesia. Makassar as a city with high growth rate is one of the cities affected by this phenomenon. One of UHI's mitigation efforts is by increasing green open spaces (RTH) in urban areas. As an effort to mitigate UHI, it is necessary to analyze the area of ??RTH and UHI in Makassar City. This study used Landsat 8 imagery in 2013 and 2018 to analyze the area of ??RTH and UHI in Makassar City. Normalized Difference Vegetation Index (NDVI) is used as indicator of vegetation coverage. Analysis was carried out in each sub-district to obtain a comparison of the vegetation area and ?UHI. The result showed that the mean temperatures in 2013 and 2018 in Makassar City had exceeded the normal threshold. The analysis shows that three sub-districts (Rappocini, Panakkukang and Makassar) have high UHI values ??followed by a reduction in vegetation area during 2013-2018. The average temperature also increased in 2013 (28.42oC) compared to 2018 (29.54oC). Based on this research, strategies for mitigating UHI were formulated for Makassar City.